EFL Lecturers’ Method for Synchronous and Asynchronous Learning through Moodle on Intensive Reading Course - Satriani, Estika; Idayani, Andi; Pryanti Kadar, Destry (J-SHMIC : Journal of English for Academic, 2025)
This research investigates intensive reading instruction at Universitas Islam Riau, Indonesia, using Moodle-based synchronous and asynchronous methods. The qualitative approach was carried out through classroom observation involving 67 students and conducting interviews with 10 students. The study found that students' reading skills enhanced  by engaging in virtual meetings and discussions during synchronous classes, while asynchronous learning allowed them to freely determine when and where to study, access educational resources such as YouTube, e-modules, some files related to materials, quizzes, and feedback. Besides that, various challenges during asynchronous learning such as students often becoming inactive on online screens, experiencing delays in receiving lectures, difficulty finding a location to improve stable internet connectivity, and inadequate access to computer devices, laptops, or smartphones that require installing and uninstalling applications repeatedly that interfere with their learning process. Challenges in asynchronous learning include difficulty understanding the learning material, excessive workload, and lack of motivation. The study recommends integrating both learning approaches for reading classes and other English classes by leveraging more of Moodle's available LMS features, as well as highlighting the importance of improving infrastructure such as stable internet and device compatibility.